2020
DOI: 10.1080/07315724.2020.1800532
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dairy Product and Dairy Protein Intake on Inflammation: A Systematic Review of the Literature

Abstract: Systemic inflammation is associated with obesity and chronic disease risk. Intake of dairy foods is associated with reduced risk of type 2 diabetes and cardiovascular disease; however, the impact of dairy foods on inflammation is not well-established. The objective of this study was to conduct a systematic review to evaluate the effect of dairy product (milk, cheese, and yogurt) and dairy protein consumption on low-grade systemic inflammation in adults without severe inflammatory disorders. A literature search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 98 publications
(176 reference statements)
1
35
0
1
Order By: Relevance
“…Many studies assessing the effect of dairy on blood lipids, and/or inflammatory markers have been carried out in adult populations, and are summarized in narrative and systematic reviews, which have suggested that dairy product intake has neutral to beneficial effects (21-23, 37, 38). The most recent of these reviews included 27 RCTs in adults without severe inflammatory disorders and concluded that dairy product and/or dairy protein consumption had no adverse effects and possibly beneficial effects on low-grade systemic inflammation; a finding that was most commonly observed in adults with OW/OB (37). None of these reviews specifically assessed these relationships in youth with/without exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies assessing the effect of dairy on blood lipids, and/or inflammatory markers have been carried out in adult populations, and are summarized in narrative and systematic reviews, which have suggested that dairy product intake has neutral to beneficial effects (21-23, 37, 38). The most recent of these reviews included 27 RCTs in adults without severe inflammatory disorders and concluded that dairy product and/or dairy protein consumption had no adverse effects and possibly beneficial effects on low-grade systemic inflammation; a finding that was most commonly observed in adults with OW/OB (37). None of these reviews specifically assessed these relationships in youth with/without exercise.…”
Section: Discussionmentioning
confidence: 99%
“…This presents a major opportunity for improving global health as higher intake of dairy foods have consistently been shown to improve health by reducing the incidence of numerous nutrient deficiencies, as well as the ability to mitigate the risk for some of the most prolific and debilitating chronic diseases, including cardiovascular disease and type 2 diabetes (28)(29)(30)(31). Notably, two recent systematic reviews focused on inflammation (which has been hypothesized to be the underlying cause of several chronic disease states), found neutral to beneficial effects of higher total dairy intake on inflammatory markers (32,33). Similarly, a growing number of systematic reviews have also consistently found neutral to beneficial effects of dairy intake on body composition and overall cardiometabolic health -with the most beneficial effects on biomarkers such as adiposity, serum lipids, blood pressure, and insulin resistance, being attributed to fermented, fortified, and/or low-fat dairy foods (34)(35)(36)(37)(38)(39).…”
Section: Dairy and Health-based Messaging In Food-based Dietary Guidelinesmentioning
confidence: 99%
“…Nutrition, along with weight, alcohol intake, physical activity, and other factors, is considered a modifiable risk factor for chronic diseases associated with systemic inflammation. Dietary factors such as fiber, antioxidants, and omega-3 fatty acids have been associated with decreased concentrations of markers of inflammation, whereas other factors such as saturated fat and sodium have been associated with increased levels of inflammation ( 28 ).…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…Systematic reviews of RCTs have evaluated the evidence linking intake of individual dairy foods with markers of inflammation and report similar results to those discussed in the sections on total dairy food intake and dairy fat intake above. The most recent systematic review ( 28 ) identified 19 RCTs on dairy food consumption that also assessed biomarkers of inflammation (CRP, IL-6, TNF-α, MCP-1, ICAM-1, and VCAM-1). Eighteen of the trials reviewed reported either no impact of dairy food intake on inflammation or an anti-inflammatory effect of dairy food intake ( 28 ).…”
Section: Current Status Of Knowledgementioning
confidence: 99%